[12]aneN3-based multifunctional compounds as fluorescent probes and nucleic acids delivering agents - Yong-Guang Gao; Shu-Yuan Huangfu; Suryaji Patil; Quan Tang; Wan Sun; Yu Li; Zhong-Lin Lu; Airong Qian (Taylor & Francis Group, 2020)
A series of multifunctional compounds (MFCs) 1a-1e based on 1,8-naphthalimide and [12]aneN3 building blocks were designed and synthesized. They were used as not only fluorescent probes for recognition of Cu2+ ions but also as non-viral gene vectors for DNA and RNA delivery. Furthermore, their complexes with Cu2+ (1-Cu) could also selectively stain lysosome in HeLa cells. In order to achieve high performance multifunctional materials, structure-performance relationship of MFCs 1a-1e was studied. It was found that MFCs 1a-1e exhibited highly selective fluorescence turn-off for Cu2+, without interference by other metal ions in aqueous solution. The fluorescence emission of 1a-1e was quenched by a factor of 10-fold, 47-fold, 6-fold, 64-fold, and 15-fold respectively in the presence of Cu2+ ions. Due to high sensitivity, good water solubility, and low cytotoxicity, MFCs 1a-1d were successfully applied in the recognition of Cu2+ and selectively staining lysosome in HeLa cells. Most importantly, MFCs 1a and 1b had excellent HeLa cell selectivity in RNA delivery, and their performances were far better than lipofectamine 2000 and 25 kDa PEI.